ANALISIS KESIAPAN KERJA SISWA DITINJAU DARI PERILAKU ENTREPRENEUR PADA SISWA SMK NEGERI 3 PONTIANAK - Vivin Dispa Sari; Warneri Warneri; Okianna Okianna (Universitas Tanjungpura, 2019)
AbstractThis study was aimed at identifying the students’ readiness to work in terms of entrepreneurship behavior at Pontianak State Vocational High School 3 students in 2019/2020 school year. The method used was a descriptive study in the form of survey research. The sources of the data in this study were the students of Pontianak State Vocational High School 3 class XII majoring in accounting consisting of 4 classes with 12 respondents for being interviewed. The results of the study showed that 1) Confidence was in the excellent category with 11 students who had a full confident attitude and 1 person was still unsure of their ability, 2) Having an initiative was in the very good category with 12 students who already showed their initiation, 3) Motivation of achievement was in the excellent category that there were 12 students who had achievement motive, 4) Posessing a leadership skill was in the very good category with 12 students who dared to be different and had a leadership skill, 5) Daring to take risks was in the good category that there were 9 students who dared to take risks and there were 3 students who did not. Keywords : Students, Work Readiness, Student Entrepreneurship Behavior